2020
DOI: 10.3390/ani10101837
|View full text |Cite
|
Sign up to set email alerts
|

Does Diversity Matter? Behavioural Differences between Piglets Given Diverse or Similar Forms of Enrichment Pre-Weaning

Abstract: This study investigated the behavioural effects of providing different enrichment materials to suckling piglets from 7 days-old until weaning. One object was attached to the pen wall (WALL), and the other was suspended in the middle of the pen (MID). Control group had the hessian fabric in both locations, and the two diverse groups had hessian and bamboo stick in alternate locations (i.e., BMID-HWALL and HMID-BWALL). Piglets behaviour was recorded on D0 (object introduction), D1, D5, D8, D12, and D14; at weani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Telkänranta et al (2014b) recorded tail damage in weaned piglets in week 9 after birth and reported that severe tail damage (part of tail missing or wounds with inflammation) was significantly less prevalent in pigs that had access to paper and ropes as enrichment materials before weaning. In line with this, Schmitt et al (2020) observed that piglets provided with diverse enrichment (one piece of hessian and one bamboo stick) during the lactation period performed less biting (chewing or biting the tail, ear or snout of another pig) in the first 2 weeks after weaning than piglets with access to one type of enrichment material only (two pieces of hessian fabric).…”
Section: Effects Of Enrichment During Lactation On Pig Behaviour Afte...mentioning
confidence: 54%
See 1 more Smart Citation
“…Telkänranta et al (2014b) recorded tail damage in weaned piglets in week 9 after birth and reported that severe tail damage (part of tail missing or wounds with inflammation) was significantly less prevalent in pigs that had access to paper and ropes as enrichment materials before weaning. In line with this, Schmitt et al (2020) observed that piglets provided with diverse enrichment (one piece of hessian and one bamboo stick) during the lactation period performed less biting (chewing or biting the tail, ear or snout of another pig) in the first 2 weeks after weaning than piglets with access to one type of enrichment material only (two pieces of hessian fabric).…”
Section: Effects Of Enrichment During Lactation On Pig Behaviour Afte...mentioning
confidence: 54%
“…In line with this, Schmitt et al. (2020) observed that piglets provided with diverse enrichment (one piece of hessian and one bamboo stick) during the lactation period performed less biting (chewing or biting the tail, ear or snout of another pig) in the first 2 weeks after weaning than piglets with access to one type of enrichment material only (two pieces of hessian fabric).…”
Section: Assessment Of the Welfare Of Farrowing And Lactating Sows An...mentioning
confidence: 79%
“…Another hypothesis is that pig behavior causes trauma to the ears providing a point of entry for bacteria to set up infection and subsequently ear necrosis [ (294,295) cited by (167)]. Young piglets already perform seemingly non-injurious ear directed behavior in commercial systems [e.g., (296)(297)(298)]. Such behavior could be a precursor to DB and therefore causative in the development of ear necrosis.…”
Section: Damaging Behavior-a Way To Spread Diseasementioning
confidence: 99%
“…Sisal rope arouses pig interest [ 15 , 16 ] more than a metal chain [ 17 ] and decreases penmate manipulation [ 18 ]. Hessian sack, also easy to bite and shake, commonly used for sows before farrowing, are also well used by young pigs and reduce damaging behaviors [ 19 , 20 ]. Wooden briquettes given to weaned pigs did not give better results on welfare indicators than a metal chain [ 21 ].…”
Section: Introductionmentioning
confidence: 99%